The UK prosthetic and orthotic workforce: current status and implications for the future - Nicola Eddison; Aoife Healy; Enza Leone; Caroline Jackson; Bracken Pluckrose; Nachiappan Chockalingam (BMC, 2024)
Abstract Background Prosthetists and orthotists (POs) are the smallest of the 14 allied health profession (AHP) workforces within NHS England. Obtaining data on the workforce has always been challenging due to this information being held across different organisations. An understanding of the prosthetic and orthotic (P&O) workforce is essential to ensure that it is adequately equipped to meet the evolving needs of users of P&O services. The study aims to estimate the size and composition, for the first time, of the UK P&O workforce and P&O service provision. Methods To gather the required information, two surveys (one for the UK P&O workforce and one for UK P&O private company) and two freedom of information (FOI) requests [one for all NHS Trusts and Health Boards (HB) in the UK and one for the higher education institutes in the UK offering programmes leading to registration as a PO were developed and distributed from September to December 2022. Results The P&O workforce survey received a 74% response rate (863 POs) and 25 private companies reported employing one or more P&O staffing groups. From the FOI requests, 181 of a potential 194 Trusts/Health Boards and all four higher education institutions responded. The study indicated a total of 1766 people in the UK P&O workforce, with orthotists and orthotic technicians representing the largest percentage of the workforce at 32% and 30%, respectively. A greater percentage of prosthetists (65%) and orthotists (57%) were employed by private companies compared to the NHS. Only 34% of POs stated that they "definitely" planned to remain in the workforce for the next 5 years. The current UK PO employment levels are 142 to 477 short of the World Health Organisation's (WHO) recommendation. Conclusions The low job satisfaction amongst many POs and the projected increase in the number of people who will require prosthetic and/or orthotic care in the UK are challenges for future UK P&O services. Strategies are required to create a sustainable and resilient workforce that can meet the needs of a changing healthcare landscape.